Managing automotive end-of-life NiMH and Li-ion batteries in Mongolia: a Material Flow Analysis to assess challenges and opportunities for circular batteries in the Global South - Prates, Luisa Ferolla Spyer; Ganbat, Gantuya; Dornack, Christina; Karthe, Daniel (Frontiers in Sustainability, 2026)
IntroductionMongolia’s transition to electric mobility presents environmental opportunities to mitigate air pollution and potentially reduce greenhouse gas emissions but also generates complex waste streams such as end-of-life (EoL) Nickel Metal Hydride (NiMH) and Lithium-Ion Batteries (LIB). This study investigates the status of Mongolia’s waste management system and how it can be optimized to enhance the circularity of such waste streams.MethodsOriginal data was collected through field research at collection, repair, storage, and disposal sites, and complemented by stakeholder interviews and an analysis of the country’s waste management legislation. Official vehicle fleet statistics (2010–2023) were used to forecast the quantity of EoL NiMH and LIB until 2050 and conduct a Material Flow Analysis for 10 different scenarios. The dataset comprises both qualitative data, describing the current waste management scenario, and quantitative data on vehicle imports, fleet composition, and battery specifications, with assumptions for missing values based on market trends.ResultsResults reveal that Mongolia lacks infrastructure and policy for safe and sustainable EoL battery management. EoL battery outflows were estimated using a two-parameter Weibull distribution model; forecast reliability was assessed via out-of-sample backcasting of the vehicle-fleet projection against historical fleet statistics (2019–2023 hold-out: MAPE = 4.71%). The results of the EoL battery quantities are scenario- and parameter-dependent projections for the lifetime and battery-specification assumptions. The results show that cumulatively (from 2023 to 2050), in the Current Scenario, 10,302 tons of EoL NiMH and 38,650 tons of EoL LIB are expected to be generated. In contrast, for the Climate Focus Scenario, 10,455 tons of EoL NiMH and 102,586 tons of EoL LIB are expected.DiscussionThe lower values of NiMH in 2050 are due to the expected transition from NiMH to LIB in HEV. Recommendations to enhance EoL battery management’s circularity include focusing on improving EoL battery collection, implementing Extended Producer Responsibility, integrating the existing informal sector, enhancing regional and international cooperation, and improving data acquisition and management. In summary, a combined approach involving local and international cooperation and socio- and technological development is essential for improving the circularity of EoL battery management in Mongolia.